Atypical Ph negative chronic myeloid leukaemia presenting as sudden profound deafness. Issue 12 (December 1991) - Smith, N; Bain, B; Michaels, L; Craven, E
Abstract : A patient with atypical Ph negative chronic myeloid leukaemia presented with the sudden onset of profound deafness. He survived only eight months. Detailed histological investigation performed at necropsy showed loss of ganglion cells and afferent nerve fibres in the cochlea and vestibule associated with extensive fibrosis and new bone formation in the labyrinthine spaces. Both leucophoresis and high dose chemotherapy capable of rapid cytoreduction are recommended in patients with chronic myeloid leukaemia with profound hearing loss, as conventional chemotherapy is rarely followed by recovery.